2018
DOI: 10.1155/2018/4701097
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Noncompliance to Antihypertensive Therapy among Hypertensive Patients Ghana: Application of Health Belief Model

Abstract: This study determined noncompliance to antihypertensive therapy (AHT) and its associated factors in a Ghanaian population by using the health belief model (HBM). This descriptive cross-sectional study conducted at Kintampo Municipality in Ghana recruited a total of 678 hypertensive patients. The questionnaire constituted information regarding sociodemographics, a five-Likert type HBM questionnaire, and lifestyle-related factors. The rate of noncompliance to AHT in this study was 58.6%. The mean age (SD) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 39 publications
(44 reference statements)
8
28
2
4
Order By: Relevance
“…Within this population of urban adults, alcohol consumption also did not have a significant effect on blood pressure control. This finding is at variance with other studies of alcohol use and hypertension in Ghana [ 35 ]. It is plausible that, in this population, alcohol consumption reported was relatively lower and thus not of significant influence.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Within this population of urban adults, alcohol consumption also did not have a significant effect on blood pressure control. This finding is at variance with other studies of alcohol use and hypertension in Ghana [ 35 ]. It is plausible that, in this population, alcohol consumption reported was relatively lower and thus not of significant influence.…”
Section: Discussioncontrasting
confidence: 99%
“…The fact that a larger proportion of patients on antihypertensive medication, however, are unable to control their blood pressure is a worrying issue. Sarfo et al [ 12 ] and Obirikorang et al [ 35 ] similarly reported that patients diagnosed over a longer period more often have poor blood pressure control. This highlights a potential predisposition of prolonged duration of the disease to a lowered motivation to control the disease and low perceived severity of the condition in such patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ghana, hypertension is the second leading cause of outpatient morbidity among adults [6], with prevalence ranging from 19 to 48% [7, 8]. The high morbidity has been associated with inadequate rates of detection, treatment, and control [6] as well as noncompliance to medication and regular checkups [9].…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic factors include demographics such as age and income [17,18]. Psychological determinants include perceived susceptibility [19,20] and trust in the care provider [21,22], and behavioral factors include forgetfulness [19,23], employment, and travel [23]. External factors include the number of medications prescribed [18], availability of prescribed medication [23], and family support [18].…”
Section: Factors Affecting Adherencementioning
confidence: 99%